A new species of Physaloptera (Nematoda: Spirurida) from Proechimys gardneri (Rodentia: Echimyidae) from the Amazon rainforest and molecular phylogenetic analyses of the genus. (2020) - Maldonado, A.; Simões, R.O.; Luiz, J. São; Costa-Neto, S.F.; Vilela, R.V.
Abstract: Nematodes of the genus Physaloptera are globally distributed and more than 100 species are known. Their life cycle involves insects, including beetles, cockroaches and crickets, as intermediate hosts. This study describes a new species of Physaloptera and reports molecular phylogenetic analyses to determine its relationships within the family Physalopteridae. Physaloptera amazonica n. sp. is described from the stomach of the caviomorph rodent Proechimys gardneri collected in the Amazon rainforest in the state of Acre, Brazil. The species is characterized by the male having the first and second pair of sessile papillae asymmetrically placed, lacking a median papilla-like protuberance between the third pairs of sessile papillae, differentiated by size and shape of the spicules, while females have four uterine branches. For both nuclear 18S rRNA and MT-CO1 gene-based phylogenies, we recovered Turgida sequences forming a clade nested within Physaloptera, thus making Physaloptera paraphyletic to the exclusion of Turgida, suggesting that the latter may have evolved from the former monodelphic ancestral state to a derived polydelphic state, or that some species of Physaloptera may belong to different genera. Relationships between most taxa within Physaloptera were poorly resolved in our phylogenies, producing multifurcations or a star phylogeny. The star-like pattern may be attributed to evolutionary processes where past simultaneous species diversification events took place. Physaloptera amazonica n. sp. formed an independent lineage, separately from the other species of Physaloptera, thus supporting the status of a new species. However, all molecular data suggested a closer relationship with other Neotropical species. In conclusion, we added a new species to this already largely diverse genus Physaloptera, bringing new insights to its phylogenetic relationships. Further analyses, adding more species and markers, should provide a better understanding of the evolutionary history of physalopterids.